2021
DOI: 10.1021/acs.jafc.1c03061
|View full text |Cite
|
Sign up to set email alerts
|

Astringent Gallic Acid in Red Wine Regulates Mechanisms of Gastric Acid Secretion via Activation of Bitter Taste Sensing Receptor TAS2R4

Abstract: Red wine is rich in phenolic compounds, which chiefly determine its characteristic taste. One of its major phenolic acid constituents for which an astringency, yet no clear contribution to bitter taste has been reported, is gallic acid (GA). In previous studies, we have demonstrated bitter-tasting constituents to regulate cellular proton secretion (PS) as a key mechanism of gastric acid secretion via activation of bitter taste sensing receptors (TAS2Rs). Here, we hypothesized a contributing role of GA to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 71 publications
1
11
0
1
Order By: Relevance
“…Furthermore, there was no effect of the nonumami-tasting compounds (e.g., cyclamate, NaCl, sucrose, citric acid, and quinine sulfate) on the RFI of refolded T1R1-VFT (p > 0.05, Figure 1F). 34,35 Receptor protein T1R3-VFT expressed as inclusion bodies in an E. coli system displayed the active function and capable of binding ligands with a fluorescence quenching manner after solubilization and refolding, 13 which was quite similar to our results.…”
Section: Activity Analysis Of T1r1-vftsupporting
confidence: 88%
“…Furthermore, there was no effect of the nonumami-tasting compounds (e.g., cyclamate, NaCl, sucrose, citric acid, and quinine sulfate) on the RFI of refolded T1R1-VFT (p > 0.05, Figure 1F). 34,35 Receptor protein T1R3-VFT expressed as inclusion bodies in an E. coli system displayed the active function and capable of binding ligands with a fluorescence quenching manner after solubilization and refolding, 13 which was quite similar to our results.…”
Section: Activity Analysis Of T1r1-vftsupporting
confidence: 88%
“…Gallic acid is an excellent astringent that exhibits anti-diarrheal effects ( Sterneder et al, 2021 ). We previously demonstrated that dietary supplementation with 0.05% GA reduced FS and exhibited antidiarrheal activity against environmental stress-induced diarrhea in puppies ( Yang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be noted that the expression of taste receptors and taste markers is not limited to taste cells. Many non-taste cell lines and non-taste tissues have been reported to express various types of elements characteristic of taste cells. , Thus, the expression of taste-related molecules alone is not a sufficient condition for characterizing cultured taste cells.…”
Section: Discussionmentioning
confidence: 99%